The Relationship between Knowledge and Length of Service of Nurses with Attitudes towards Patient Safety at Oto Iskandar Regional Hospital in Nata, Bandung 2025 - Megawati, Dede Sri; Indriyati, Titi; Prahastuti, Brian Sri (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Hospitals are important institutions in providing health services to the community with the main task of providing curative (healing) and preventive (preventive) services. Curative services focus on the diagnosis, treatment, and care of patients, while preventive services aim to prevent the emergence of diseases through vaccination and education on healthy lifestyles. Patient safety is an important aspect in health services that guarantee patient safety and prevent unexpected events. Nurses as primary health workers play a very important role in the implementation of patient safety. To determine the relationship between knowledge and length of service of nurses with attitudes towards patient safety in the Inpatient Installation of Oto Iskandar Hospital in Nata Bandung. The study used a quantitative approach with a cross-sectional design, involving 94 nurses as respondents. Statistical analysis showed that there was a significant relationship between knowledge and attitudes of nurses (p = 0.000, OR = 11.8), as well as between length of service and attitudes of nurses (p = 0.003, OR = 4.1). In addition, demographic factors such as gender and age also contribute to variations in nurses' attitudes. The research model explained 63% of the variation in attitudes towards patient safety. Hospitals need to strengthen training and supervision, especially for nurses with less than 5 years of service. Further research is recommended to examine the implementation of patient safety more comprehensively to continuously improve service quality and patient safety. The research findings are expected to serve as a basis for strengthening training, supervision, and a culture of patient safety in hospitals to reduce incidents and improve service quality.